Research on Big Data Strategy of Telecom Carriers Based on Information Value Chain Theory - Chengyi Tao; Xiaomei Ma (Dianxin kexue)
Starting from the concept and characteristics of big data,the theoretical connection between big data and information value,as well as information chain was discussed.From the perspective of information value chain,a theoretical derivation was made on enterprise' big data strategy and based on that,value-added mechanisms of big data in telecom carrier's operating activities were specially explored.Finally the concrete suggestions to telecom carriers on the following areas of big data:data input terminal,data flow field and data output terminal were given.